Monsters of Mental Health - Corner, Creative (Journal of Pakistan Psychiatric Society, 2022)
ThewidespreaddepictionofMentalillnessesintheeyesofcommonmanisdistortedduetotheimages portrayed in media. Mental health issues like any other illness can affect any one and havebeenobservedas1inevery8peopleglobally.Mentaldisordersinvolvesignificantdisturbancesinthinking,emotionalregulation,orbehaviourandmayleadtoabnormalbeliefsandperceptionsofthe self which are further exaggerated and stigmatized by the society. We need to be tolerant andacceptingoftheseindividualsbyaddressingthisstigmaandconsideringthemasapartofthebiologicalcurve.